Derivative of a function y = f(x) is represented as f'(x) or

$\frac{dy}{dx}$ or y' or

$\frac{d}{dx}$ [f(x)] or Df(x).

**The basic rules of Differentiation of functions in calculus are shown below along with examples:**1)

Derivative of a constant function.The derivative of a function f(x) = c where c is a constant is given by f '(x) = 0.

**Example:** If f(x) = 7, then f'(x) = 0.

2)

Derivative of a power function (power rule).The derivative of a function f(x) = $x^n$ where n is a constant

real number is given by f'(x) = n $x^{n-1}$.

**Example:** If f(x) = $x^4$, then f'(x) = $4x^3$.

If f(x) = $x^{-5}$ then f’(x) = -5$x^{(-5-1)}$ = -5$x^{-6}$ = -

$\frac{5}{x^6}$.

3)

Derivative of a function multiplied by a constant.The derivative of a function f(x) = c g(x) is given by f'(x) = cg'(x).

**Example:** If f(x) = 5$x^4$, then find f'(x).

Solution: Let c = 5 and g(x) = $x^4$, then f'(x) = cg'(x) = 5(4$x^3$) = 20$x^3$.

4)

Derivative of the sum of functions (sum rule).The derivative of a function f(x) = g(x) + h(x) is given by f'(x) = g'(x) + h'(x)

**Example:** If f(x)= 5$x^4$ + 9, then find f'(x).

Solution: let g(x) = 5$x^4$ and h(x) = 9, then f'(x) = g'(x) + h'(x) = 20$x^3$ + 0 = 20$x^3$.

5)

Derivative of the difference of functions.The derivative of a function f(x)= g(x) - h(x)is given by f'(x) = g'(x) - h'(x).

**Example:** If f(x) = x 3 - x -2, then find f'(x).

Solution: Let g(x) = $x^5$ and h(x) = $x^{-2}$, then, f'(x) = g'(x) - h'(x) = 5$x^4$ - (-2 $x^{-3}$) = 5$x^4$ + 2$x^{-3}$.

6)

Derivative of the product of two functions (product rule or Leibniz rule).The derivative of a function f(x) = g(x) h(x) is given by f'(x) = g'(x) h(x) + g(x)h'(x).

It is also represented as (UV)’ = U’V + U V’.

**Example:** f(x) = ($x^3$ - 3x) (x - 3).

Solution: Let g(x) = ($x^3$ - 3x) and h(x) = (x - 3), then

f'(x) = g(x) h'(x) + h(x) g'(x) = (3$x^2$ - 3) (x-3) + ($x^3$ - 3x) (1)

=3 $x^3$ - 9 $x^2$ - 3x + 9 + $x^3$ - 3x = 4$x^3$ - 9$x^2$ - 3x + 9

7)

Derivative of the quotient of two functions (quotient rule).The derivative of a function f(x) =

$\frac{g(x)}{h(x)}$ is given by f^'(x) =

$\frac{g'(x)h(x)- g(x)h(x)}{(h(x))^2}$ **Example:** f(x) =

$\frac{x – 5}{x + 7}$.

Solution: Let g(x) = (x - 5) and h(x) = (x + 7), then f'(x) =

$\frac{g'(x)h(x)- g(x)h(x)}{(h(x))^2}$ =

$\frac{((1)(x + 7) - (x - 5)(1))}{(x + 7)^2}$ =

$\frac{(x + 7) - (x-5)}{(x+7)^2}$ =

$\frac{x + 7 - x + 5}{(x+7)^2}$ =

$\frac{12}{(x+7)^2}$.

8)

Derivative of a logarithmic function.The derivative of f(x) = $log_b$x is given by f'(x) =

$\frac{1}{(x\ lnb)}$If f(x) = ln x, then f'(x) = $\frac{1}{x}$. **Example:** Find the derivative of f(x) = $log_5$x

Solution: Applying the formula mentioned above we get,

f'(x) =

$\frac{1}{(x\ ln\ 5)}$.

**Example:** Find the derivative of f(x) = ln x + 3$x^2$

Solution: Let g(x) = ln x and h(x) = 3$x^2$, Using the sum rule, f'(x) = g'(x) + h'(x), we get

f'(x)=

$\frac{1}{x}$ + 6x.

9)

Derivative of an exponential function.The derivative of an

exponential function f(x)= $e^x$ with respect to x is f^'(x)= $e^x$

The derivative of an exponential function with base a, f(x) = $a^x$ with respect to x is f'(x) = $a^x$ ln a

**Example:** Find the derivative of f(x)= 7$e^x$.

Solution: The derivative of the function f(x)= 7$e^x$ is given by 7 f'($e^x$) = 7$e^x$.

**Example:** Find the derivative of f(x)= $7^x$.

Solution: The derivative of the function f(x)= $7^x$ is given by f'($7^x$) = $7^x$ ln 7.

10)

Derivatives of Trigonometric functions. The derivatives of the six trigonometric functions are tiven as below:

(sin x)’ = cos x. (cot x)’ = -$csc^2$ x.

(cos x)’ = -sin x. (sec x)’ = sec x tan x.

(tan x)’ = $sec^2$ x. (csc x)’ = -csc x cot x.

11)

Derivatives of Inverse Trigonometric functions.(arcsin x)' =

$\frac{1}{\sqrt{1 - x^2}}$(arccos x)' =

$\frac{1}{\sqrt{1 - x^2}}$(arctan x)' =

$\frac{1}{\sqrt{1 + x^2}}$(arcsec x)' =

$\frac{1}{|x|\sqrt{x^2 - 1}}$(arccsc x)' =

$\frac{1}{|x|\sqrt{x^2 - 1}}$(arccot x)' =

$\frac{1}{1 + x^2}$12)

Derivatives of Hyperbolic functions.(sinh x)' = cosh x =

$\frac{e^x + e^{-x}}{2}$(cosh x)' = sinh x =

$\frac{e^x - e^{-x}}{2}$(tanh x)' = sec$h^2$ x

(sech x)' = -tanh x sech x

(csch x)' = -coth x csch x

(coth x)' = -csc$h^2$ x

(arsinh x)' =

$\frac{1}{\sqrt{x^2 + 1}}$(arcosh x)' =

$\frac{1}{\sqrt{x^2 - 1}}$(artanh x)' =

$\frac{1}{1 - x^2}$(arsech x)' = -

$\frac{1}{x \sqrt{1 - x^2}}$(arcsch x)' =

$\frac{1}{|x| \sqrt{1 + x^2}}$(arcoth x)' =

$\frac{1}{1 - x^2}$13)

Chain rule of differentiation.Let f(x) = (g o h)(x) = g(h(x)) and u = g(x).

Let y = f(u); then the derivative of f with respect to x, f'(x) is given by:

f'(x) = (

$\frac{dy}{du}$) (

$\frac{du}{dx}$).

**Example:** Find the derivative f'(x), if f is given by f(x) = 5cos(2x - 3)

Solution: Let u = 2x - 3 and y = 5cos u, hence

$\frac{du}{dx}$ = 2 and

$\frac{dy}{du}$ = -5 sin u

Using the chain rule, f'(x) = (

$\frac{dy}{du}$)(

$\frac{du}{dx}$) = -5sin(u)(2) = -10sin(u)

Substituting back, u = 2x - 3 in sin(u), we get f'(x) = -10sin (2x - 3).